'Happiness for mankind' : Achaemenian religion and the imperial project - Lincoln, Bruce (Acta Iranica, 2012)
The product of twenty years' research, this is the first book to study the way religious concerns permeated Achaemenian culture, deeply influencing such varied things as categories of space, time, number and causality, constructions of nature, humanity and moral order, institutions of law, education and kingship, practices of diplomacy, tribute, irrigation and gardening (including the sumptuous royal gardens designated as "paradises)". Particular attention is devoted to the role of cosmogonic myths, dualistic ethics, demonological beliefs, the ideology of royal charisma, the sense of Persia as a sacred center and the conviction that Achaemenian rulers bore unique responsibility for restoring the world's lost perfection and realizing God's plans for creation: a task to be accomplished by reuniting the globe's tragically fragmented peoples.